SOSIALISASI DAN PELATIHAN PEMBUATAN ROTI DENGAN RAGI KHAMIR LOKAL SACCAROMYCES CEREVISAE - Kusmiyati, Nur; Kusnadi, Joni; Denta, Anggeria Oktavisa (STAI Darul Qalam Tangerang, 2023)
The Community Development Program (CDP) broadly aims to provide insight, education and skills in the culinary field to improve family welfare, especially in the people of Sitirejo Village, Wagir District, Malang Regency. The knowledge and skills provided to the community are knowledge about utilizing the local yeast Saccharomyces cerevisae to make bread and to process various types of good and nutritious bread. The planned CDP activities will be held in March-August 2023, at the Sitirejo Village Hall. The target of PPM participants is the Sitirejo Village community who are members of the Family Welfare Empowerment Group (PKK) under the auspices of the Community Development Service and the Population Control and Family Planning Village. The methods used include lectures, discussions and questions and answers, as well as the practice of making various breads using the local yeast Saccharomyces cerevisae. The results of the CDP activities were analyzed using descriptive techniques with percentage values. Based on the results of the CDP activities, it was shown that participants gained new knowledge about local yeast. In addition, CDP training participants are also skilled at making various breads using local yeast. CDP activities are expected to provide an overview related to the catering business to CDP training participants